Impacts from air pollution on respiratory disease outcomes: a meta-analysis - Su, Jason G.; Aslebagh, Shadi; Shahriary, Eahsan; Barrett, Meredith; Balmes, John Randolph (Frontiers in Public Health, 2024)
Introduction: Air pollution is widely acknowledged as a significant factor in respiratory outcomes, including coughing, wheezing, emergency department (ED) visits, and even death. Although several literature reviews have confirmed the association between air pollution and respiratory outcomes, they often did not standardize associations across different studies and overlooked other increasingly impactful pollutants such as trace metals. Recognizing the importance of consistent comparison and emissions of non-exhaust particles from road traffic, this study aims to comprehensively evaluate the standardized effects of various criteria pollutants and trace metals on respiratory health. Methods: We conducted a meta-analysis of peer-reviewed journal articles on air pollution and respiratory outcomes published between January 1, 2000, and June 1, 2024. The study included children (<18 years), adults (≥18 years), and all age groups exposed to criteria pollutants established by the U.S. Environmental Protection Agency National Ambient Air Quality Standards, and over 10 trace metals. Using databases such as PubMed, Medline, Web of Science Core Collection, and Google Scholar, we identified 579 relevant papers. After rigorous screening and quality assessment using the Newcastle-Ottawa Scale, 50 high-quality studies were included. We converted various reported outcomes (e.g., odds ratios, relative risk, percent increase) to a standardized odds ratio (OR) for meta-analyses. Results: Our meta-analysis indicated significant associations between air pollutants and respiratory outcomes. For particulate matter with diameter ≤ 2.5 microns (PM2.5), the overall ORs for children, adults, and combined age groups were 1.31, 1.10, and 1.26, respectively, indicating a consistent positive association. Similar positive associations were observed for particulate matter with diameter ≤ 10 microns (PM10) and other pollutants, with children showing higher susceptibility than adults. The analysis of trace metals also showed significant associations; however, these findings require cautious interpretation due to the small number of studies. Conclusion: Our study supports associations between air pollutants, including non-exhaust trace metals, and respiratory outcomes across different age groups. The findings underscore the need for stringent environmental health policies and further research, especially in regions with higher pollution levels. Future studies should consider long-term and short-term exposures separately, and include diverse populations to improve the accuracy and generalizability of the results.